GREEN INTELLECTUAL CAPITAL CONSERVATISM EARNING MANAGEMENT, TO FUTURE STOCK RETURN AS MODERATING STOCK RETURN (Study of Mining Companies in Indonesia Listed on IDX for the Period of 2014-2019) - Fitri Dwi Febrianti; Sugiyanto Sugiyanto; Juwita Ramandani Fitria (STIE Binaniaga, 2020)
This study aims to analyze The Moderating Stock Rreturn of Green Intellectual Capital, Conserva- tism, and Real Earning Management on Future Stock Returns on mining companies listed on the Indo- nesia Stock Exchange Period 2014 - 2019. This type of research is quantitative research in which this research is done by explaining the results of data from the calculation of numbers that are calculated and analyzed. The analysis used in this research is regression analysis, where regression analysis esti- mates the magnitude of the coefficients resulting from a linear equation involving one independent variable to be used as a predictor of the value of the dependent variable. The results of this study indi- cate that Intellectual capital has a significant effect on future stock returns, Conservatism has a signifi- cant effect on future stock returns, Earning management has a significant effect on future stock returns, Simultaneous results Green Intellectual capital, conservatism, earning management simultaneously have an effect on future stock returns, the moderating future stock return on stock returns. These find- ings indicate that in sample companies, future stock returns on stock returns have no implications